(untitled) (Itinera, 2023)
This article aims to explore patterns of the creative process in which performance faces ecological thought, placing about sustainability strategies. Many scholars have investigated the relationship between theatre and ecology since the end of the XXth century. Two positions have emerged strongly: ecology as a metaphor (Marranca) or as a performative tool (Chaudhuri). We will reflect on more recent points of view (Giannachi Stewart, Theresa J May, Baz Kershaw) and try to relate them to sustainability science (Bologna). Then, it will be important to focus on two phases of the creative process, dramatization, and staging, to understand the evolution of artistic practices about environmental issues. Finally, we are going to apply the methodological pattern outlined by the theoretical and practical analysis to two case studies: weLAND (2021), a contemporary circus show that staged climate migration, and La möa (2022), a choreographic work in nature that embodied the relationships in the river habitat.